Volatility spillover between Exchange-Traded Funds on the Johannesburg Stock Exchange - Starr, Caleb (Department of Finance and Tax, 2025)
Growth in the Exchange-Traded Fund industry (ETF) has been exponential in the past decade. International research on this topic has been extensive, with less focus given to the local Johannesburg Stock Exchange (JSE). This research aims to extend the existing literature on the JSE, particularly focusing on the volatility spillover between domestic ETFs representing four major asset classes and four equity ETFs using the Diebold and Yilmaz (2012) Spillover Index. The equity ETF system includes the Satrix RESI 10 (STXRES), Satrix FINI 15 (STXFIN), and Satrix Capped INDI (STXIND). Four ETFs are selected as proxies for equities, bonds, commodities, and property. The ETFs representing the asset classes are the Satrix 40 (STX40), Satrix GOVI (STXGVI), ABSA NewGOLD (GLD), and 1Invest SA Property (ETFSAP), respectively. These two volatility systems are examined independently. The results show that the STX40 ETF is a net volatility transmitter in the alternate asset ETF system. Within the equity ETF system, the STXFIN and STXRES are net volatility receivers, and the STXIND fluctuates between receiver and transmitter of volatility over the period analysed. In the alternate asset system, ETFSAP and STXGVI are net volatility receivers, with the GLD ETF oscillating between being both a net receiver and transmitter. Furthermore, the Chicago Board Options Exchange Volatility Index (VIX) index is used to proxy foreign volatility shocks to South African financial assets. Approximately 12,5% of volatility for the full set of ETFs can be attributed to the VIX. Additionally, a regression analysis is employed to evaluate the VIX as a significant explanatory variable for measuring volatility propagation through the chosen ETFs, with the results confirming its significance solely in the equity ETF system. This study adds to the existing literature on portfolio allocation decisions by focusing on sector rotation and asset allocation strategies. Additionally, it provides insights into the diversification opportunities that JSE investors can benefit from using ETFs. The study includes periods of financial market volatility, driven by significant macroeconomic events, such as Britain's referendum vote on European Union participation, the COVID-19 pandemic, and the conflict between Russia and Ukraine